The Relationship between the Effectiveness of Nurses' Therapeutic Communication and the Quality of Inpatient Services Based on Patient Perceptions at Hospital X, Kota Kediri - Anggraini Setiyarini; David Raditya Soehartono; Salmaqonita Khusnul Irvani Sari; Sahat Manampin Siahaan; Safari Hasan; Agus Sulistiawan (Journal of Health Educational Science And Technology, 2026)
Background: Lack of skills in therapeutic communication can affect the patient's treatment process and impact the quality of services in health facilities. Data collection was carried out through questionnaires, and data analysis used the Chi Square statistical test. The results showed that 57% of respondents indicated that nurses' therapeutic communication was in the good category, and 63% of respondents assessed that the quality of nursing services was also good. The Chi Square test analysis produced a p-value of 0.000, which indicated a relationship between therapeutic communication and the quality of nursing services. Purpose: This study aims to determine whether there is a relationship between the effectiveness of nurses' therapeutic communication and the quality of inpatient services based on patient perceptions at Hospital X, Kediri Regency. Method: This study used a quantitative observational analytical research design with a cross-sectional design. The sampling technique used in this study was the cluster random sampling method. The following are the names of the rooms in this study: Cendana, Flamboyan, Seruni, Melati, Bugenville, Anggrek, and Teratai. Each room was taken 15 samples. The total sample was 105. Results: The results of this study showed that the results of the statistical test p-value were 0.000 (<0.005); it can be concluded that there is a relationship between the effectiveness of nurses' therapeutic communication and the quality of inpatient services based on patient perceptions at Hospital X, Kediri Regency. Conclusion: There is a relationship between the effectiveness of nurses' therapeutic communication and the quality of inpatient services based on patient perceptions at Hospital X, Kediri Regency.